1989
DOI: 10.1159/000169594
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Renal Failure Complicated by Cerebral Oedema

Abstract: Dialysis disequilibrium due to cerebral oedema still causes a significant degree of both morbidity and mortality. We discuss the management of 5 such cases and demonstrate the improved stability during treatment with continuous veno-venous haemofiltration. This may be due to the improved osmotic stability during haemofiltration with a resultant decrease in the osmotic gradient across the blood-brain barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This reflects the fact that post‐OLT patients are frequently haemodynamically unstable. Continuous therapy is the preferred therapy for patients with fulminant hepatic failure as it can minimize the volume changes and osmotic shifts that occur during dialysis, thereby reducing the risk of cerebral oedema and intra‐cranial hypertension (27–29).…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the fact that post‐OLT patients are frequently haemodynamically unstable. Continuous therapy is the preferred therapy for patients with fulminant hepatic failure as it can minimize the volume changes and osmotic shifts that occur during dialysis, thereby reducing the risk of cerebral oedema and intra‐cranial hypertension (27–29).…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, for patients who are at risk of or who have increased intracranial pressure including neurosurgical patients, patients with encephalitis or acute liver failure, studies have demonstrated the benefits of prevention of the surge in intracranial pressure. [16][17][18] The future trend of the use of RRT modality in ICUs may change as a number of results of recent published studies favoring CRRT on the clinical outcomes. In 2014, Wald et al 19 reported the findings of their retrospective cohort study conducted between July 1996 and December 2009.…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, disturbances in renal function result directly from liver failure or its hemodynamic consequences. Early initiation of continuous renal replacement therapy15, 16 affords tight control of intravascular volume, thereby minimizing the potential for pulmonary and cerebral edema. Intensive renal replacement therapy with daily hemodialysis was of benefit for critically ill patients in comparison with the standard of care 17.…”
Section: Acute Liver Failure As a Paradigm For Sepsis With Respect Tomentioning
confidence: 99%